2012
DOI: 10.1099/jmm.0.040600-0
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni infection and virulence-associated genes in children with moderate to severe diarrhoea admitted to emergency rooms in northeastern Brazil

Abstract: Campylobacter is an important cause of foodborne gastroenteritis. We determined the occurrence of Campylobacter jejuni and Campylobacter coli, using culture-based methods and PCRs targeting virulence-associated genes (VAGs) among children aged ¡14 years who were treated for diarrhoea at emergency rooms in northeastern Brazil. Genomic DNA was extracted directly from stool samples collected from 366 children. A questionnaire was also applied to qualify the clinical conditions presented by each child at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 47 publications
4
13
4
1
Order By: Relevance
“…This finding is in agreement with the studies by other investigators who did not find vir B11 gene among Campylobacter isolates of children from Brazil and Bangladesh [23, 24]. However, a few other studies indicated the prevalence of vir B11 to be 10.7-22.7% among clinical isolates [21, 25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in agreement with the studies by other investigators who did not find vir B11 gene among Campylobacter isolates of children from Brazil and Bangladesh [23, 24]. However, a few other studies indicated the prevalence of vir B11 to be 10.7-22.7% among clinical isolates [21, 25].…”
Section: Discussionsupporting
confidence: 92%
“…infections in children with moderate to severe diarrhea [21-23]. Similarly, these genes were also detected within all of our isolates.…”
Section: Discussionsupporting
confidence: 71%
“…Implementation of the molecular tools increased the detection frequency of enteric pathogens 3-fold (19.2% compared to 6.4% with conventional methods) (7). Moreover, a considerable proportion of positive fecal samples previously confirmed as negative by culture methods have been detected by using molecular tools (14). The present study validated a multiplex PCR assay for the detection of hemorrhagic bacteria in stool samples.…”
Section: Discussionmentioning
confidence: 69%
“…simultaneously in stool, but results were seen within 4 h in comparison to 3 to 5 days by conventional methods. Although there are numerous reports on PCR assays for the detection of hemorrhagic bacteria (15,16), only a few of these assays have incorporated internal controls (14,17). The presence of PCR inhibitors (like bilirubin, bile salts, and heme in the feces) in stool samples may inhibit amplification and limit the usefulness of the PCR technique (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates were recorded from chicken giblets (23·5%) compared to duck (19%), turkey (14·5%) and squab (4%) [25]. Previous studies in other countries have also identified C. jejuni as the most common isolate in poultry with C. coli being more frequently isolated from pigs and sheep [14,[26][27][28][29]. Generally, the population of pigs in Egypt is much lower than the poultry populations due to the popular consumption of poultry and the large-scale government culling of around 300 000 pigs during the 2009 H1N1 'swine flu' pandemic [30].…”
Section: Discussionmentioning
confidence: 96%